JOGOS MATEMÁTICOS: UMA METODOLOGIA PARA AUXILIAR O APRENDIZADO DO ALUNO EM SALA DE AULA - Barbosa Caçandre, Elemilson; Barroso, Poliana; Victor Silva Guimarães, João; Lima Lopes, Leonardo; Torres, Herbert (LINKSCIENCEPLACE, 2026)
It is notorious that many students have great difficulty in learning the contents of mathematics and that because of this fact many scholars in the field of education have been engaged in researching new and diverse ways to eradicate this existing deficiency. The main objective of this study is to discuss the way in which students meet when they are received in high school, especially in public schools and the level they present when tested by institutional tests and especially the National High School Examination. On the other hand, to present how the mathematical games can be part of the teaching methodology in these institutions, in order to maximize the students' learning. In this perspective, it can be observed that some students forget some basic mathematics, not being able to develop other contents introduced by the teachers. The present study is based on a bibliographical research, in which there were consultations in books and periodicals.